2022
DOI: 10.7150/thno.74974
|View full text |Cite
|
Sign up to set email alerts
|

AKR1C3-dependent lipid droplet formation confers hepatocellular carcinoma cell adaptability to targeted therapy

Abstract: Rationale: Increased lipid droplet (LD) formation has been linked to tumor metastasis, stemness, and chemoresistance in various types of cancer. Here, we revealed that LD formation is critical for the adaptation to sorafenib in hepatocellular carcinoma (HCC) cells. We aim to investigate the LD function and its regulatory mechanisms in HCC. Methods:The key proteins responsible for LD formation were screened by both metabolomics and proteomics in sorafenib-resistant HCC cells and further validated by immunoblott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…As a result, we aimed to confirm whether inhibiting SMPD2 or CSTA enhances the sensitivity of liver cancer cells to lapatinib (Figure 11B). Additionally, it is worth noting that SMPD2 is mainly located on lipid droplets and plasma membranes (Figure 8B), and lipid droplet formation is known to confer resistance of HCC cells to chemotherapy (43). This may partly explain why lapatinib increases the sensitivity of HCC cells to SMPD2 inhibition.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As a result, we aimed to confirm whether inhibiting SMPD2 or CSTA enhances the sensitivity of liver cancer cells to lapatinib (Figure 11B). Additionally, it is worth noting that SMPD2 is mainly located on lipid droplets and plasma membranes (Figure 8B), and lipid droplet formation is known to confer resistance of HCC cells to chemotherapy (43). This may partly explain why lapatinib increases the sensitivity of HCC cells to SMPD2 inhibition.…”
Section: Discussionmentioning
confidence: 98%
“…Alterations in the levels of certain genes involved in sphingolipid metabolism may have a significant impact on the effectiveness of chemotherapy (42,43). Using gene expression data from different risk subgroups, we utilized the pRRophetic package to predict variations in the sensitivity to clinical antitumor drugs across different risk groups (Supplementary Table S2; Figure 10).…”
Section: Inhibition Of Spgs Makes Hcc Cells Sensitive To Lapatinib Drugmentioning
confidence: 99%
“…Lipids are reported to be an important energy source to fuel tumour progression and metastasis 7 . In addition, studies have confirmed lipid droplets (LDs) and lipogenesis play an important role in the development and stemness of HCC 8–11 …”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, studies have confirmed lipid droplets (LDs) and lipogenesis play an important role in the development and stemness of HCC. [8][9][10][11] SKP-Cullin1-F-box (SCF) complexes have been suggested to play important roles in multiple processes including adipogenesis and lipogenesis. 12,13 The typical biological function of the SCF complex is to induce the degradation of various substrates through ubiquitination.…”
Section: Introductionmentioning
confidence: 99%
“…In CRC cells, LDs are crucial players in tumorigenicity and development 10 . They were also reported to participate in resistance to drug therapy 11 . Chemotherapeutics treatment significantly increased LD content 12 .…”
Section: Introductionmentioning
confidence: 99%